TEORI PERILAKU PEMBELIAN BERULANG (STUDI KASUS TIKTOK SHOP) - Hidayatulloh, M. Syarif Hidayatulloh; Indra Hastuti; Esti Dwi Rahmawati (Cahaya Ilmu Bangsa, 2024)
ABSTRAKPenelitian ini bertujuan mengidentifikasi pengaruh keterikatan kebiasaan dan keterikatan emosional terhadap pembelian ulang di TikTok Shop, dengan mempertimbangkan niat beli ulang sebagai variabel penengah. Penelitian ini menggunakan sampel dari orang yang telah melakukan pembelian berulang di TikTok Shop. Variabel yang digunakan adalah keterikatan kebiasaan, keterikatan emosional, niat beli ulang, dan pembelian ulang. Data dikumpulkan melalui observasi dan kuesioner. Teknik analisis menggunakan metode Structural Equation Modeling-Part Least Square (SEM-PLS) dengan program SmartPLS4. Hasil penelitian menunjukkan bahwa keterikatan kebiasaan dan keterikatan emosional berpengaruh positif dan signifikan terhadap niat beli ulang dan pembelian ulang. Niat beli ulang juga berpengaruh positif dan signifikan terhadap pembelian ulang serta memediasi pengaruh keterikatan kebiasaan dan keterikatan emosional terhadap pembelian ulang.Kata Kunci : Keterikatan Kebiasaan, Keterikatan Emosional, Niat Beli Ulang, Pembelian Ulang, SmartPLS4 ABSTRACTThis study aims to identify how habit attachment and emotional attachment influence repeat purchases on TikTok Shop, considering repurchase intention as a mediating variable. By understanding the factors that influence consumers to make repeat purchases on TikTok Shop, this research aims to provide valuable insights for TikTok Shop management in designing more effective marketing strategies to enhance customer loyalty. The sample consists of people who have made repeat purchases on TikTok Shop. The variables used in this study include habit attachment, emotional attachment, repurchase intention, and repeat purchase. Data collection methods include observation and questionnaires, using both primary and secondary data. The analysis technique employs Structural Equation Modeling-Part Least Square (SEM-PLS) with the SmartPLS4 program. The results show that habit attachment positively and significantly influences repurchase intention and repeat purchase, emotional attachment positively and significantly influences repurchase intention and repeat purchase, and repurchase intention positively and significantly influences repeat purchase. Repurchase intention also positively and significantly mediates the relationship between habit attachment and repeat purchase, as well as between emotional attachment and repeat purchase.Keywords : Habbittual Attachment, Emotional Attachment, Repurchase Intention, Repeat Purchase, SmartPLS4